Tauhid dalam Konsepsi Abdurrauf (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
Abdurauf bin Ali al Fansuri is a productive scholar that wrote many books, which one of them is ‘Umdat al-Muhtajin Ila Suluk Maslak al-Mufradin. The book explains zikir in detail through Tarekat Syattariyah and other related applications to reach the knowledge of Tauhid. The book is consisted of two chapters. The first chapter discusses about ma’rifat (knowledge about Allah) through kalami approach. The discussion is around the existence, attribute and substance of Allah.
Keywords: Tauhid; Abdurrauf; Ketuhanan